Integrated Log Interpretation in the Chinese Continental Scientific Drilling Main Hole (Eastern China): Lithology and Mineralization - AMA Salim, HP Pan, M Luo, F Zhou, . (2008)
Delineation of lithology and mineralization of different rock units of the Chinese Continental Scientific Drilling Main Hole (CCSD-MH), Eastern China, is the main objective of this study. Different logging operations were conducted in the studied area. Subduction and metamorphism lead to high compressional wave velocity (Vp) and low neutron density (CNL) values of different rocks.